Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Consider the function [tex]\( f(x)=\frac{x^2}{7x^2+8} \)[/tex].

List the [tex]\(x\)[/tex] values of the inflection points of [tex]\( f \)[/tex]. If there are no inflection points, enter 'NONE'.

[tex]\(\square\)[/tex]


Sagot :

To find the inflection points of the function [tex]\( f(x)=\frac{x^2}{7 x^2+8} \)[/tex], we need to analyze the second derivative of this function. Inflection points occur where the second derivative changes sign, which corresponds to the points where the second derivative is equal to zero.

The process is as follows:

1. First Derivative: Calculate the first derivative of [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = \frac{x^2}{7x^2 + 8} \][/tex]
Using the quotient rule:
[tex]\[ f'(x) = \frac{(2x)(7x^2 + 8) - (x^2)(14x)}{(7x^2 + 8)^2} = \frac{14x^3 + 16x - 14x^3}{(7x^2 + 8)^2} = \frac{16x}{(7x^2 + 8)^2} \][/tex]

2. Second Derivative: Compute the second derivative from the first derivative:
[tex]\[ f''(x) = \frac{d}{dx} \left( \frac{16x}{(7x^2 + 8)^2} \right) \][/tex]
Applying the quotient rule again:
[tex]\[ f''(x) = \frac{(16)(7x^2 + 8)^2 - (16x)(2)(7x^2 + 8)(14x)}{(7x^2 + 8)^4} = \frac{16(7x^2 + 8)^2 - 448x^2(7x^2 + 8)}{(7x^2 + 8)^4} \][/tex]
Simplify the expression in the numerator:
[tex]\[ 16(7x^4 + 16x^2 + 8) - 896x^4 = 112x^4 + 128x - 896x^4 = 128x - 784x^4 \][/tex]
So the second derivative can be represented as:
[tex]\[ f''(x) = \frac{16(7x^4 + 16x^2 - 56x^4)}{(7x^2 + 8)^2} = \frac{16(-49x^4 + 16x^2)}{(7x^2 + 8)^3} = \frac{16(-49x^4 + 16x^2)}{(7x^2 + 8)^3} \][/tex]

3. Setting the Second Derivative Equal to Zero: Solve for [tex]\( x \)[/tex] in:
[tex]\[ -784x^2(7x^2 - 8) = 0 \][/tex]
This equation simplifies to:
[tex]\[ 112x^4 + 128x^2 = 0 \][/tex]
Since [tex]\(-49x^2(7x^2 - 8) = 0\)[/tex]

[tex]\[ 784x^4 - 112(7x^2 - 8)=0 784x^4 + 128x^2 \][/tex]

This gives roots at:
[tex]\[ x = \pm \frac{2\sqrt{42}}{21} \][/tex]

Therefore, the [tex]\( x \)[/tex] values of the inflection points of [tex]\( f(x) = \frac{x^2}{7x^2 + 8} \)[/tex] are:
[tex]\[ x = -\frac{2\sqrt{42}}{21} \text{ and } x = \frac{2\sqrt{42}}{21} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.